2004
DOI: 10.1111/j.1365-2036.2004.01928.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐directed strategy to reduce prescribing for patients with dyspepsia in general practice: a randomized trial

Abstract: SUMMARYBackground: The percentage of patients receiving long--term treatment with acid suppressive drugs, mainly proton pump inhibitors, is higher than the prevalence of diseases that are commonly accepted as the proper indication for long-term proton pump inhibitor use. Aim: To evaluate whether a patient-directed intervention (direct mail) reduced the prescription of antisecretory medication for dyspepsia in general practice. Methods: A cluster-randomized trial was performed. One hundred and thirteen chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 13 publications
5
40
0
1
Order By: Relevance
“…These studies show that in more than 50% of patients on continuous PPI therapy, significant symptoms of gastro-oesophageal reflux disease (GERD) and dyspepsia are present. 4,5 Additionally, trial-based evidence has shown that simple patient-directed intervention is able to reduce longterm PPI use without affecting dyspepsia severity or quality of life. 5 Patients on long-term PPI and without…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that in more than 50% of patients on continuous PPI therapy, significant symptoms of gastro-oesophageal reflux disease (GERD) and dyspepsia are present. 4,5 Additionally, trial-based evidence has shown that simple patient-directed intervention is able to reduce longterm PPI use without affecting dyspepsia severity or quality of life. 5 Patients on long-term PPI and without…”
Section: Introductionmentioning
confidence: 99%
“…We developed and successfully tested a letter of discontinuation for patients. 19 Another study found that some patients with nonspecific low back pain resisted advice to stay physically active and avoid passive physiotherapy. We developed and successfully tested a training session for physicians that included training in communication skills.…”
Section: Linking Interventions To These Barriersmentioning
confidence: 99%
“…Also, the preferences of those with mild dementia (who have been shown to be able to express preferences for treatment 43,44 ) need to be studied. Future research should focus on the development of a guide to assist GPs in discussing medication discontinuation with older adults and their carers as well as continued efforts towards education and patient-directed deprescribing interventions (which have shown some effectiveness 45,46 ). In addition, the role of pharmacists and nurses in deprescribing needs to be further explored to facilitate deprescribing in practice.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%